Pelatihan Penyusunan LKPD Digital Interaktif Terintegrasi Islam untuk Menguatkan Nilai Moderasi Beragama Guru SMP/MTs Di Kota Malang - Masamah, Ulfa; Abdussakir; Harithiya, Avida Faustina (Transformatif : Jurnal Pengabdian Masyarakat, 2024)
This service program aims to provide training in preparing digital-interactive teaching materials based on religious moderation for teachers in the LP Ma'arif NU environment in Malang City. This activity includes the method of implementing this service using Participatory Action Research (PAR) with a cycle of work steps, namely to know, to understand, to plan, to act, and to change. The results of the training showed that the participants were enthusiastic about participating in the program, 46,67% were very enthusiastic, 36,67% were enthusiastic, and 16,67% they were neutral. In addition, 80% of participants have successfully completed digital-interactive teaching materials based on religious moderation which can then be implemented in classroom learning as product diversification in the LP Ma'arif NU environment in Malang City.